Adversarialism in informal, collaborative, and 'soft' inquisitorial settings: lawyer roles in child welfare legal environments. Issue 4 (2nd October 2019) - Porter, Robert; Welch, Vicki; Mitchell, Fiona
ABSTRACT: This article explores the challenges and benefits of increased legal representation in child welfare hearings, with reference to the Scottish Children's Hearings System. We look at the role and impact of adversarial behaviours within legal environments intended to follow an informal, collaborative approach. We analyse the views of 66 individuals involved in the Hearings System, including reporters, social workers, panel members and lawyers, collected through four focus groups and 12 interviews held in 2015. We place this analysis in the context of previous research. Our findings identify concern about adversarialism, inter-professional tensions and various challenges associated with burgeoning legal representation. Difficulties stem from disparate professional values and perceived threats to the ethos of hearings. We conclude it is difficult, but possible, to incorporate an adversarial element into such forums. Doing so may help to protect rights and potentially improve decision-making for children and families. The article concludes by considering implications for the practice of lawyers and others.